KLASIFIKASI HARTA WARISAN SAAT BUJANGAN DAN SETELAH MENIKAH DI DESA SIBIRUANG KABUPATEN KAMPAR, RIAU - Mardianis, Mardianis (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2023)
The shift in the role of wealth for men who are single and women who are still girls, which is a gender issue in society. So that Islamic inheritance law must also be able to accommodate the needs of the village community for laws that can provide justice for marriage in the present. Where there are differences in the calculation of the division in Islamic inheritance law. Where is the separation between the status of assets when married and assets when single. The formulation of the problem in this study is how to review Islamic law on the grouping of inherited assets when bachelors and after marriage in Sibiruang Village. The purpose of this study was to analyze the review of Islamic law on the grouping of inheritance when bachelors and after marriage in Sibiruang Village. This research is a type of field research (field research) with descriptive analysis method through data collection by observation, interviews and documentation. Furthermore, the existing data is collected and analyzed through a review of Islamic law by referring to the arguments and opinions of experts. The results of this study show the conclusion that the distribution of inheritance during bachelors and marriage is muhdats in religion, there is not a single argument that defines this issue. The grouping of inherited assets is something that is qat'i from Allah SWT because the texts of the proposition are classified as verses of muhkam. The explanation for the distribution carried out in Sibiruang Village is to carry out ijtihad al-Istislahi, this is an inaccurate decision, because ijtihad al-Istislahi will be used in tasawur al-Mas'alah when the bayan's argument cannot provide an answer, while the case for inheritance very clear and obvious. A wife is never hindered from obtaining an inheritance and is never prevented from getting an inheritance, it's just that the wife's share can be reduced by 1/8 (hijab nuqhsan) due to the presence of her husband's child. If she does not have children from her husband, the stipulation is that the wife gets ¼ as well as sons and daughters